The impact of challenge-hindrance research stress on burnout among healthcare workers: the moderating role of perceived organizational support - Chen, Xianglan; Jian, Chengping; Shen, Xiaohong; Liu, Ruixue; Pu, Yuan; Wang, Shuhua (Frontiers in Public Health, 2025)
ObjectiveThis study explores the impact of challenge-hindrance research stress on burnout among healthcare workers and examines the moderating role of perceived organizational support (POS). The findings aim to provide suggestions for alleviating burnout in healthcare workers.MethodsData were collected using the Demographic Questionnaire, Burnout Scale, Research Stress Scale, and Perceived Organizational Support Scale. Relationships and moderation effects were analyzed via SPSS and PROCESS Macro.ResultsBoth challenge research stress (r = 0.156, p < 0.05) and hindrance research stress (r = 0.403, p < 0.01) were significantly positively correlated with burnout. Linear regression revealed that POS significantly negatively moderated the relationship between hindrance research stress and burnout (β = −0.137, p < 0.05). PROCESS analysis indicated that hindrance research stress was significantly associated with low POS (β = 0.460, p < 0.001), but not significant at high POS (β = 0.159, p > 0.05). No significant moderating role of POS was found between challenge research stress and burnout.ConclusionMedical institutions should focus on reducing hindrance research stress while implementing organizational support interventions, including optimized resource distribution and procedural streamlining to mitigate burnout. Regarding challenge research stress, strategies should emphasize the enhancement of individual self-management capabilities.